Helicobacter pylori Type IV Secretion System and Its Adhesin Subunit, CagL, Mediate Potent Inflammatory Responses in Primary Human Endothelial Cells - Tafreshi, Mona; Guan, Jyeswei; Gorrell, Rebecca J.; Chew, Nicole; Xin, Yue; Deswaerte, Virginie; Rohde, Manfred; Daly, Roger J.; Peek, Richard M.; Jenkins, Brendan J.; Davies, Elizabeth M.; Kwok, Terry (Frontiers in Cellular and Infection Microbiology, 2018)
The Gram-negative bacterium, Helicobacter pylori, causes chronic gastritis, peptic ulcers, and gastric cancer in humans. Although the gastric epithelium is the primary site of H. pylori colonization, H. pylori can gain access to deeper tissues. Concurring with this notion, H. pylori has been found in the vicinity of endothelial cells in gastric submucosa. Endothelial cells play crucial roles in innate immune response, wound healing and tumorigenesis. This study examines the molecular mechanisms by which H. pylori interacts with and triggers inflammatory responses in endothelial cells. We observed that H. pylori infection of primary human endothelial cells stimulated secretion of the key inflammatory cytokines, interleukin-6 (IL-6) and interleukin-8 (IL-8). In particular, IL-8, a potent chemokine and angiogenic factor, was secreted by H. pylori-infected endothelial cells to levels approximately 10- to 20-fold higher than that typically observed in H. pylori-infected gastric epithelial cells. These inflammatory responses were triggered by the H. pylori type IV secretion system (T4SS) and the T4SS-associated adhesin CagL, but not the translocation substrate CagA. Moreover, in contrast to integrin α5β1 playing an essential role in IL-8 induction by H. pylori upon infection of gastric epithelial cells, both integrin α5β1 and integrin αvβ3 were dispensable for IL-8 induction in H. pylori-infected endothelial cells. However, epidermal growth factor receptor (EGFR) is crucial for mediating the potent H. pylori-induced IL-8 response in endothelial cells. This study reveals a novel mechanism by which the H. pylori T4SS and its adhesin subunit, CagL, may contribute to H. pylori pathogenesis by stimulating the endothelial innate immune responses, while highlighting EGFR as a potential therapeutic target for controlling H. pylori-induced inflammation.